ANALISA KINERJA KEUANGAN PEMERINTAHKABUPATEN LAMONGAN TAHUN ANGGARAN 2009-2013 - RIZKA HENDYTA, AMANDA (Jurnal Akuntansi AKUNESA, 2015)
This research aimed to analyze the financial performance of Lamongan District fiscal year 2009-2013. This research method using descriptive method with secondary data. To measure the performance of this government to use some ratios, including independence ratio, the dependency ratio, the ratio of fiscal decentralization, effectiveness ratio, efficiency ratio, and the ratio of revenue growth. Results of the research showed that the ratio of 10.96% which means the independence of Lamongan district quite independent in funding through the regional interest revenue received. Lamongan District dependency ratio 2009-2013 fiscal year showed an average of 75.22%, which means